Variable speed drives introduction to VSD - Primedia Workplace Learning ([United States] : PRIMEDIA Workplace Learning)
The Introduction to Variable Speed Drives training program, or unit, is designed to familiarize trainees with the operation and use of variable speed drives. After completing this program, the trainees should be able to identify different types of DC and AC drives and explain how they control motor operation.
Keywords: Variable speed drives; Electric driving